Screening for hypertension among older adults: A primary care "High Risk" approach - John Jacob; Muliyil Jayaprakash; Balraj Vinohar (Wolters Kluwer Medknow Publications, 2010)
Background: Recommendations for early detection and management of elevated blood pressure through opportunistic clinic-based screening may be inadequate for the rural population in India as access to health facilities is limited. Materials and Methods: Sixteen Health Aides (trained primary care workers) were trained to measure blood pressure using a standardized training procedure. Six of those assessed competent in initial evaluation were allotted a stratified random sample of about 150 persons each, 50 years or over, in the village under their care to measure blood pressures during their regular scheduled visits. Results: 14/16 of the health aides (83%) met the stipulated criteria for the simulation study using a module from British Hypertension Society. In the field survey of 920 individuals where 20% of the population was evaluated by a blinded investigator, the weighted Kappa for agreement, using normal, pre-hypertension and hypertension as categories, ranged between 62% and 89%. Only 75/286 (25%) of those detected to be hypertensive knew their status prior to the study. All those detected with hypertension were referred to a physician at a referral facility. 70% of those referred were evaluated at the referral facility and 64% of them initiated on treatment for hypertension within 3 months. Conclusion: Using primary care workers to screen for hypertension through the model suggested here will ensure that the population over 50 years of age will be screened once every 2 years without burdening the worker. This screening process will enable the health system to identify and cater to needs of this vulnerable population.